Comparison of VO2max Prediction of Submaximal Exercise Testing for Six Minute Arm Ergometer Test with Six Minute Walking Test in Untrained Healthy Young Adult Males - Taufan Hartawan; Andriati Andriati; Nurul Kusuma Wardani (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Six-minute walking test (6-MWT) is one of the submaximal exercise testing that is commonly used. The 6-MWT has limited use in the condition of individuals with limited limbs. Therefore, a six-minute arm ergometer test (6-MAT) submaximal exercise testing was developed. The presence of 6-MAT for assessing VO2max prediction is still relatively small.Aim: To compare the predicted VO2max of 6-MWT and 6-MAT, and to see if there are differences in each predicted VO2max value.Material and Methods: This was a cross-sectional study with a consecutive sampling, involving 31 untrained healthy young adult males, aged 26-40 years old. Each subject underwent two exercise testing 6-MWT and 6-MAT, which were carried out on different days with a minimum washout period of 24 hours. VO2max prediction value was evaluated for each exercise testing on each subject.Results: There are significant differences between the predicted VO2max values of 6-MWT and 6- MAT (p = 0.00). The mean VO2max prediction values of 6-MAT is higher than 6-MWT with 2288.43 mL.min-1 and 1573.72 mL.min-1, respectively.Conclusion: The 6-MAT could be used for assessing VO2max prediction of individuals, although, there is a difference value between the predicted VO2max of the 6-MWT and 6-MAT submaximal exercise testing, with the VO2max value of the 6-MAT higher than the 6-MWT submaximal exercise testing.